2017
DOI: 10.1111/tra.12471
|View full text |Cite
|
Sign up to set email alerts
|

Routes and mechanisms of post‐endosomal cholesterol trafficking: A story that never ends

Abstract: Mammalian cells acquire most exogenous cholesterol through receptor-mediated endocytosis of low-density lipoproteins (LDLs). After internalization, LDL cholesteryl esters are hydrolyzed to release free cholesterol, which then translocates to late endosomes (LEs)/lysosomes (LYs) and incorporates into the membranes by co-ordinated actions of Niemann-Pick type C (NPC) 1 and NPC2 proteins. However, how cholesterol exits LEs/LYs and moves to other organelles remain largely unclear. Growing evidence has suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 144 publications
(216 reference statements)
0
69
0
1
Order By: Relevance
“…The upregulation of GATA2 in intima-infiltrating macrophages and the dysregulation of multiple cholesterol-processing genes in the same cells suggest that GATA2 overexpression may drive defects in macrophage cholesterol homeostasis. RT-PCR analysis of intimainfiltrating macrophages confirmed that NPC1 and NPC2, which mediate the transfer of endocytosed cholesterol to cytosolic carrier proteins 43 , and ABCA1, which mediates the export of cholesterol from cells 6 , were downregulated in intima-infiltrating macrophages ( Figure 3A-C). This alteration in cholesterol uptake and efflux has previously been associated with abnormal cholesterol processing and foam cell development 44,45 .…”
Section: Gata2 Partially Regulates Macrophage Cholesterol Homeostasismentioning
confidence: 86%
“…The upregulation of GATA2 in intima-infiltrating macrophages and the dysregulation of multiple cholesterol-processing genes in the same cells suggest that GATA2 overexpression may drive defects in macrophage cholesterol homeostasis. RT-PCR analysis of intimainfiltrating macrophages confirmed that NPC1 and NPC2, which mediate the transfer of endocytosed cholesterol to cytosolic carrier proteins 43 , and ABCA1, which mediates the export of cholesterol from cells 6 , were downregulated in intima-infiltrating macrophages ( Figure 3A-C). This alteration in cholesterol uptake and efflux has previously been associated with abnormal cholesterol processing and foam cell development 44,45 .…”
Section: Gata2 Partially Regulates Macrophage Cholesterol Homeostasismentioning
confidence: 86%
“…Cellular cholesterol homeostasis depends critically on sterol flux through LE/LYSs, but the pathways and molecular mechanisms of sterol trafficking between these organelles and other membranes are poorly defined 51,52 . In Niemann-Pick type C2 disease, cholesterol and other lipids build up due to lack of a small sterol-transfer protein, NPC2, in the lumen of LE/LYSs.…”
Section: Discussionmentioning
confidence: 99%
“…One set, the ORP discussed above in relation to PS enrichment, may transfer cholesterol to the plasma membrane. There are 12 family members in mammalian cells (27). The second set of cholesterol transfer proteins are StARD proteins containing START domain (Steroidogenic acute regulatory protein related lipid transfer) domain(s).…”
Section: Transfer Of Cholesterol Among Cellular Membranesmentioning
confidence: 99%